2006
DOI: 10.1190/1.2213951
|View full text |Cite
|
Sign up to set email alerts
|

Improved Green’s functions for passive-source structural studies

Abstract: Over the past two decades, teleseismic receiver functions have proved to be a useful tool to investigate crustal structure. Because they represent a first-order approximation to the Swave component of the teleseismic-P Green's function, receiver functions provide valuable information on physical properties related to shear modulus. However, the implicit use of the P-component seismogram as a proxy for the source precludes the recovery of information on discontinuous structure involving contrasts in compression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…For a typical crustal thickness, P pMs arrives ~10 s after P with a positive polarity, while P sMs has a negative polarity and arrives ~18.5 s after P (e.g., see Fig. 5 of Mercier et al, 2006). When treated as primaries in this migration algorithm these multiples would map to the approximate depths of the two features tagged with question marks in Figure 2.…”
Section: Mantle Discontinuitiesmentioning
confidence: 95%
“…For a typical crustal thickness, P pMs arrives ~10 s after P with a positive polarity, while P sMs has a negative polarity and arrives ~18.5 s after P (e.g., see Fig. 5 of Mercier et al, 2006). When treated as primaries in this migration algorithm these multiples would map to the approximate depths of the two features tagged with question marks in Figure 2.…”
Section: Mantle Discontinuitiesmentioning
confidence: 95%
“…Finally, the receiver function spectral phase is reconstructed by exploiting the minimumphase nature of the direct-component trace. The details of this methodology are presented elsewhere [Baig et al, 2005;Bostock, 2004;Mercier et al, 2006], and the application to temporary array recording and S wave data was demonstrated by Hansen and Dueker [2009]. We note several advantages afforded by this approach.…”
Section: Scattered Wave Imagingmentioning
confidence: 99%
“…, whereas the phase of the two remaining quantities can be recovered through a slightly more involved procedure described by Mercier et al (2006). An example showing the teleseismic P Green function estimates as a function of horizontal slowness for station HYB at Hyderabad, India, is shown in Figure 5.…”
Section: Improved Teleseismic P Green Functionsmentioning
confidence: 99%
“…In fact, the phase of all three components of motion (or, more specifically, upgoing P, SV, and SH), as well as the source, need not be considered until their respective amplitude spectra have been recovered. As explained by Baig et al (2005) and Mercier et al (2006), estimation of, for example, the source amplitude spectrum can be accomplished by considering the cross spectrum of two seismograms sharing that source. As an example, consider two components P and SV of the same three-component recording represented in the frequency domain as P(o), V(o).…”
Section: Improved Teleseismic P Green Functionsmentioning
confidence: 99%